2016
DOI: 10.1007/s12350-016-0505-4
|View full text |Cite
|
Sign up to set email alerts
|

Budget impact of applying appropriateness criteria for myocardial perfusion scintigraphy: The perspective of a developing country

Abstract: Myocardial perfusion imaging is widely used for the risk stratification of coronary artery disease. In view of its cost, besides radiation issues, judicious evaluation of the appropriateness of its indications is essential to prevent an unnecessary economic burden on the health system. We evaluated, at a tertiary-care, public Brazilian hospital, the appropriateness of myocardial perfusion scintigraphy indications, and estimated the budget impact of applying appropriateness criteria. An observational, cross-sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 29 publications
0
16
0
1
Order By: Relevance
“…In contrast, Gibbons et al reported a significant decrease in the proportion of inappropriate MPI scans performed in a single academic center after publications of the 2009 AUC 30. Furthermore, a recent budget impact analysis showed that application of the 2009 AUC could result in savings of 18.6% in a single tertiary care hospital in Brazil 31. To our knowledge, no studies have assessed the impact of the AUC on utilization rates of noninvasive cardiac diagnostic testing (including MPI) at the population level.…”
Section: Discussionmentioning
confidence: 96%
“…In contrast, Gibbons et al reported a significant decrease in the proportion of inappropriate MPI scans performed in a single academic center after publications of the 2009 AUC 30. Furthermore, a recent budget impact analysis showed that application of the 2009 AUC could result in savings of 18.6% in a single tertiary care hospital in Brazil 31. To our knowledge, no studies have assessed the impact of the AUC on utilization rates of noninvasive cardiac diagnostic testing (including MPI) at the population level.…”
Section: Discussionmentioning
confidence: 96%
“…A recent study showed that SPECT MPI is widely used for diagnostic and risk stratification purposes in the United States and patient’s socio-economic status did not significantly affect the use of SPECT MPI by physicians[15]. In the developing world several studies have shown the widespread use of SPECT MPI by physicians to aid in diagnosis in management[16,17]. One such report from Iran regarding SPECT MPI referral practices showed that 72.5% (211/291) of the referrals found to be appropriate per ASNC recommendations[16].…”
Section: Discussionmentioning
confidence: 99%
“…25 A significant body of literature demonstrated that appropriate MPI use enhances its acumen in risk stratification, reduces radiation risk, and improves its clinical value. [27][28][29][30][31][32][33] Physicians are faced with multiple, occasionally discordant, AUC from different organizations. For example, there is substantial discordance between the multimodality AUC for the detection and risk assessment of stable ischemic heart disease developed by the American College of Cardiology, ASNC, and several other societies and the Appropriateness Criteria set forth by the American College of Radiology (ACR).…”
Section: Appropriate Use Reportingmentioning
confidence: 99%